The Mahmud Abu Rayyah’s Contribution to The Development of Ulumul Hadith - Muhammad Fauzhan 'Azima (Institut Agama Islam Sumatera Barat, 2024)
This article explains about Mahmud Abu Rayyah and his contribution to the development of ulumul hadith. The book Adhwa' 'ala al-Sunnah al-Muhammadiyah written by Mahmud Abu Rayyah is the primary source in this research. Meanwhile, other writings related to Mahmud Abu Rayyah and his hadith thoughts are secondary sources. The research methods used in this article are qualitative research methods with the type of library research, documentation studies as data collection techniques, and analytical descriptive methods as data analysis methods. The results of the study show that Mahmud Abu Rayyah's contribution to the development of ulumul hadith is: First, cleaning the hadith and ulumul hadith from israiliyyat. Mahmud Abu Rayyah doubted the truth of israiliyyat and rejected its use in the study of hadith and ulumul hadith. Second, promoting a rational approach and a historical approach in the study of hadith and ulumul hadith. The two approaches that Mahmud Abu Rayyah often uses are very important in the development of ulumul hadith. Third, campaigning for the validity test of hadith through two stages, namely sanad criticism and matan criticism. Mahmud Abu Rayyah criticized hadith scholars who only attach importance to the criticism of sanad and ignore the criticism of matan. Matan criticism, in Mahmud Abu Rayyah's view, must also be carried out and be the final determinant of whether or not a hadith is shahih or not.